Symbolism Contained in The Secret Garden by Frances Hodgson Burnett - Aryunianto, Andreas Fernando (Universitas Negeri Padang, 2024)
This study aims at indentifying the kinds of Symbols and finding the dominant of the Symbols that are found in The Secret Garden novel. What type of symbols in The Secret Garden by Frances Hodgson Burnett and the meaning of symbols found. This research uses descriptive qualitative method by taking sources from a book by Frances Hodgson Burnett entitled The Secret Garden, looking for and describing in detail the symbols that exist. Data in the novel is analyzed using the theory of Symbols. The results of this study show that there 9 kinds of symbols; green, black, earth, water, sun, bird, seeds, rose, and garden which has different meaning. The symbols that appear are Frances' views in interpreting an object, so that it can be understood in her literary works. The dominant Symbols found in The Secret Garden novel are Garden. The garden is the main theme in the novel which has a symbol as affection. In analyzing it, the first thing to do is to read the entire novel and understand which ones have symbols in them. The advice from future researchers is to understand the symbols contained in several classifications to distinguish, so be careful in concluding the meaning of symbols in the novel with same interpretation. This study is important to know the message or meaning that the author wants to convey in Frances work.